The role of the educational inspectorate on higher music studies as non-university higher education - Marzal Raga, Reyes (Avances en Supervisión Educativa, 2022)
In the present study, higher music studies are analyzed as part of higher artistic education that make up non-university higher education. In the context of our educational system, with a traditional binary division between university and non-university education, the definition of a hybrid legal regime for these studies generates dysfunctions that require regulatory improvements in the definition of these studies, their teaching staff and the centers in question. that are taught Having identified these regulatory failures, the purpose of the work is to point out to what extent the educational inspection services carry out the functions of legality control and guarantee of educational quality that are their own, making it clear from the beginning that the degree of autonomy recognized to the Higher Music Conservatories do not evade their submission to the tutelage of the Educational Administration. The methodology of the study is that of the legal sciences, which combines the normative sources with the doctrinal and jurisprudential positions of application. The author maintains a long line of research on the legal regime of musical education from an administrative law approach.